'More people talk to you when you have a dog' – dogs as catalysts for social inclusion of people with intellectual disabilities. Issue 10 (19th August 2018) - Bould, E.; Bigby, C.; Bennett, P. C.; Howell, T. J.
Abstract: Background: Research has shown Australian group homes, and supported living options, fail to support people with intellectual disabilities (IDs) to develop social connections. This pilot study evaluates the effectiveness of a visiting dog walking program to facilitate encounters with other community members. Method: Sixteen adults with IDs were assigned to one of two groups, matched on key characteristics. Group 1 had 14, 1‐hour outings in the community with a dog and their handler; Group 2 had 14 outings with a handler alone, followed by an additional five outings with a handler and a dog. Within and between group differences were analysed according to number of encounters when a dog was present and absent. Qualitative data provided insights into the nature of these encounters. Results: The number of encounters was significantly higher when a dog was present than when participants went out into the community with a handler alone. This pattern was reflected in the qualitative data, which also suggested the presence of a dog helped to break social norms about speaking to strangers and discourage disrespect towards people with IDs. Conclusions: A dog walking program has the potential to encourage convivial encounters, which in the long term could be catalysts to help people with IDs build social connections in their communities; this should be further explored.